Refractory absence seizures: An Italian multicenter retrospective study. (November 2015) - Franzoni, Emilio; Matricardi, Sara; Di Pisa, Veronica; Capovilla, Giuseppe; Romeo, Antonino; Tozzi, Elisabetta; Pruna, Dario; Salerno, Grazia Gabriella; Zamponi, Nelia; Accorsi, Patrizia; Giordano, Lucio; Coppola, Giangennaro; et al.
Abstract Background To evaluate evidence and prognosis of refractory cases of absence seizures. Methods Subjects with refractory absence seizures were identified retrospectively in 17 Italian epilepsy pediatrics Centers. We analyzed age at onset, family history, presence of myoclonic components, seizure frequency, treatment with antiepileptic drugs (AEDs), interictal electroencephalography (EEG) and neuropsychological assessment. Two subgroups were identified: one with patients with current absence seizures and another with patients that had become seizure free with or without AED treatment. The chi-square test was applied. Results A total of 92 subjects with drug-resistant absence seizures were analyzed. 45 subjects still show absence seizures (49%) and the other 47 became seizure free (51%) after a period of drug-resistance. The statistical analysis between these two groups showed no correlation between age of onset, family history and abnormalities at interictal EEG. Statistically significant differences were observed with regard to the number of AEDs used and intellectual disability. Conclusion Typical absence epilepsy classifiable as Childhood Absence Epilepsy could not be considered so "benign", as suggested in literature. A longer duration of disease and a higher frequency of seizure seem to be correlated with a higher presence of cognitive impairment. No significant risk factor was observed to allow the faster and better recognition of patients with worse prognosis.